MNEs and flexible working practices in Mauritius - Richard Croucher; Marian Rizov (The International Journal of Human Resource Management, 2015)
We compare how far companies based in Africa, India and the 'global North' operating in Mauritius adopt high-trust flexible working practices and how these are linked to different clusters of wider labour management practice. Using comprehensive firmlevel data collected in late 2011, we find that African/Indian company practices are closer to those of indigenous firms than to those of Northern companies. The different company groups operate in quite different ways but regional multi-national enterprises operate in a similar way to indigenous companies. We therefore conclude that Rugman and Verbeke's 'regionalization' theory also applies to the HR field. We further find that both a relatively strategic approach to HRM and measures to develop employer- employee interdependence are, respectively, linked directly and indirectly to flexible working incidence.
Keywords: M54; M52; M14; 330; employer–employee interdependence; flexible working; multinational enterprises; regionalisation; strategic HRM